5th ESO-ESMO international consensus guidelines for advanced breast cancer (ABC 5) - Cardoso, F (2020)
This ESO-ESMO ABC 5 Clinical Practice Guideline provides key recommendations for managing advanced breast cancer patients. It provides updates on managing patients with all breast cancer subtypes, LABC, follow-up, palliative and supportive care. Updated diagnostic and treatment algorithms are also provided. All recommendations were compiled by a multidisciplinary group of international experts. Recommendations are based on available clinical evidence and the collective expert opinion of the authors.